[(Z)-O-Ethyl N-(4-chlorophenyl)thiocarbamato-κS](triphenylphosphine-κP)gold(I) dichloromethane hemisolvate - Tadbuppa, Primjira P. (International Union of Crystallography, 2010)
The Au(I) atom in the title compound, [Au(C(9)H(9)ClNOS)(C(18)H(15)P)]·0.5CH(2)Cl(2), exists within a slightly distorted linear geometry defined by an S,P donor set [S—Au—P angle = 178.01 (4)°]; a close intramolecular Au⋯O contact [2.964 (4) Å] also occurs. In the crystal structure, molecules are linked into supramolecular chains propagating along [010] by C—H⋯N, C—H⋯S and C—H⋯π interactions. The solvent molecule is disordered about a twofold rotation axis.